PHANTOM LIMB PAIN IN AMPUTEES: PATHOPHYSIOLOGICAL MECHANISMS AND THERAPEUTIC APPROACHES (International Integralize Scientific, 2026)
Phantom pain is a condition frequently reported by individuals who have undergone amputation, characterized by the perception of pain in a missing limb. The present study aims to analyze the main pathophysiological mechanisms involved in phantom pain, as well as the therapeutic approaches described in the literature. This is a narrative review with a qualitative approach, conducted through the analysis of scientific articles published in databases such as PubMed, SciELO, and Google Scholar, considering publications from 1996 to 2023 in Portuguese and English. Studies addressing neurophysiological mechanisms and treatment strategies for phantom pain were included, while those without a direct relationship to the topic were excluded. The results indicate that phantom pain is associated with peripheral, spinal, and central mechanisms, with emphasis on cortical reorganization, neuroma formation, and central sensitization. Furthermore, it was observed that therapeutic approaches include pharmacological and non-pharmacological interventions, although a universally effective treatment has not yet been established. It is concluded that phantom pain has a multifactorial etiology, necessitating an interdisciplinary and individualized approach for its clinical management.
Keywords: Phantom pain; amputation; neuropathic pain; neuroplasticity; treatment.